PENGARUH ASPEK KELENGKAPAN PRODUK, PERSEPSI HARGA, KUALITAS PELAYANAN DAN KENYAMANAN BERBELANJA TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN (STUDI KASUS PADAPERMATA CELL KOTA PANGKALPINANG) - Anggraeni, Veliani; Zamhari, Zamhari; Astuti , Nelly (Jurnal Ilmiah Niaga Bisnis Elektronik, 2021)
This research was entitled in Bahasa Indonesia: “Pengaruh Aspek Kelengkapan Produk, Persepsi Harga, Kualitas Pelayanan dan Kenyamanan Berbelanja Terhadap Keputusan Pembelian Pelanggan (Studi Kasus pada Permata Cell Kota Pangkalpinang)”. This research was conducted during pandemic of Covid-19 (April 2021-June 2021) and it was administrated in City of Pangkalpinang and consists of 80 pages without attachments. The purpose of this study was to determine how strong the effect of the Product Completeness, Price Perception, Service Quality and Shopping Convenience on Customer Purchasing Decision at Permata Cell. This study runs by using quantitative data analysis and was using a Multiple Linear Regression Analysis along with Coefficient of Determination. The results of the analysis state that the product completeness variable has no effect on customer purchasing decision with the results (t-count (-1,722) while t-table 1,661), in other words (t-count value (-1,722) < t-table value 1,661) or value of significance 0,088 > 0,05 then clearly H1 is rejected. The results of the analysis state that the price perception variable has negative effect on customer purchasing decision with the results (t-count (-3,255) while t-table 1,661), in other words (t-count value (-3,255) < t-table value 1,661) or value of significance 0,001 < 0,05 then clearly H2 is accepted. The results of the analysis state that the service quality variable has negative effect on customer purchasing decision with the results (t-count (-4,260) while t-table 1,661), in other words (t-count value (-4,260) < t-table value 1,661) or value of significance 0,001 < 0,05 then clearly H3 is accepted. The results of the analysis state that the shopping convenience variable has negative effect on customer purchasing decision with the results (t-count (-3,155) while t-table 1,661), in other words (t-count value (-3,155) < t-table value 1,661) or value of significance 0,002 < 0,05 then clearly H4 is accepted. As simultaneously or together, it shows that the variables of product completeness, price perception, service quality and shopping convenience have a significant effect on customer purchasing decision with the results of F-count 11,437 and F-table value of 2,47. In other words, Fcount (11,437) > Ftable (2,47). ), therefore it is shown that H0 is rejected and H5 is accepted. With the coefficient of determination obtained a value of 0,325, which means that the effect of the product completeness variable, price perception, service quality and shopping convenience simultaneously at 32,5%, and the remaining 67,5% is explained by other independent variables not used in this study.